Quantifying glucose uptake at the single cell level with confocal microscopy reveals significant variability within and across individuals - Joel D. Paprocki; Patrick J. Macdonald; Yongjin Xu; Alan Cheng; Timothy C. Dunn; Sergey Y. Tetin (Scientific Reports)
Abstract Measurement of glycated hemoglobin (HbA1c) in human red blood cells plays a critical role in the diagnosis and treatment of diabetes mellitus. However, recent studies have suggested large variation in the relationship between average glucose levels and HbA1c, creating the need to understand glucose variability at the cellular level. Here, we devised a fluorescence-based method to quantitatively observe GLUT1-mediated intracellular glucose analog tracer uptake in individual RBCs utilizing microfluidics and confocal microscopy. For the first time, we demonstrate that intracellular/extracellular tracer percentages can be measured at the single cell level using the fluorescently labeled glucose analog, 2-NBDG. A small donor panel study indicates that the characteristic intracellular 2-NBDG percentages can statistically differ based on race (i.e., Caucasian/Hispanic vs Black). RBC intracellular glucose analog tracer 2-NBDG levels show significant variability both from cell-to-cell and from donor-to-donor. This specific transport mechanism will affect HbA1c formation in erythrocytes. This finding further supports a more personalized, and perhaps improved, diagnostic strategy for diabetes.